الدور السياسي والاجتماعي للفعاليات الاجتماعية بالجزائر العثمانية(1519-1830م) الصوفية والعلماء نموذجا - سعودي سميحة (جامعة محمد بوضياف بالمسيلة, 2025)
تناولت هذه الدراسة الدور السياسي والاجتماعي للفعاليات الاجتماعية في الجزائر خلال العهد العثماني وذلك من خلال تركيزي على الصوفية والعلماء كنموذجين رئيسيين حيث لعبتا دورا محوريا في إدارة المجتمع وتوجيه التفاعل مع السلطة العثمانية والمساهمة في الحفاظ على استقرارالبلاد فعلى مستوى السياسي شكلت الصوفية والعلماء حلقة وصل بين السكان والسلطة العثمانية إذ ساهم شيوخ الزوايا في ضبط الأمن أما العلماء فقد كانوا عنصرا أساسيا في المؤسسات الرسمية مثل: القضاء والإفتاء والتعليم. أما الجانب الاجتماعي فقد كانت زوايا الصوفية مركزا متعددة الوظائف حيث جمعت بين التعليم والإغاثة والتكافل الاجتماعي ونشر الأخلاق والقيم الإسلامية. This study examines the political and social role of social actors in Algeria during the Ottoman era, focusing on Sufism and scholars as two key models. Both played a central role in managing society, guiding interactions with the Ottoman authority, and contributing to the stability of the country. On the political level, Sufi orders and scholars acted as intermediaries between the population and the Ottoman authority. Sufi sheikhs contributed to maintaining security, while scholars were essential figures in official institutions such as the judiciary, fatwa issuance, and education. On the social level, Sufi lodges (zawiyas) served as multifunctional centers, combining education, relief, social solidarity, and the promotion of Islamic morals and values